Discrepancies Between Nomenclature and Indications of Psychotropics - Minami, Fusaka; Zohar, Joseph; Suzuki, Takefumi; Koizumi, Teruki; Mimura, Masaru; Yagi, Gohei; Uchida, Hiroyuki (Pharmacopsychiatry, 2019)
Introduction While the current nomenclature of psychotropic drugs is disease-based, their approved indications do not always match their classifications.Methods Information on approved indications of “second-generation antipsychotics” and “newer antidepressants” that are available in the United States (US), the United Kingdom (UK), France, Germany, and Japan were extracted from their packet inserts.Results A significant proportion of “atypical antipsychotics” were approved for psychiatric conditions other than psychotic disorders (i. e., bipolar disorder, major depressive disorder, and autistic disorder) as follows: 76.9% in the US, 66.7% in the UK, 66.7% in France, 60.0% in Germany, and 44.4% in Japan. Likewise, more than half of “newer antidepressants” had approved indications for psychiatric conditions other than depression (e. g., panic disorder, obsessive compulsive disorder, social anxiety disorder, general anxiety disorder, and post-traumatic stress disorder): 56.3% in the US, 69.2% in the UK, 69.2% in France, 50.0% in Germany, and 62.5% in Japan.Conclusions Our results raise concerns regarding generic terminologies of “antipsychotics” and “antidepressants” since the conventional indication-based nomenclature does not fit well with the official indication.
Keywords: antidepressant; antipsychotic; indication; NbN; neuroscience-based nomenclature